Analysis of Factors Influencing the Financial Behavior of the Young Generation - Sarumaha, Cindy K.; Bu’ulolo, Nanny A.; Zebua, Serniati; Zai, Kurniawan S. (Manunggal Halim Jaya, 2025)
This study aims to determine the influence of financial literacy factors, income levels, and financial experience on the financial behavior of students of the Faculty of Economics, Nias University. The data collection method in this study uses primary data obtained from the results of filling out questionnaires to 95 respondents of students of the Faculty of Economics, Nias University, as well as secondary data obtained from journals related to this study. The data analysis methods used are validity test, reliability test, correlation coefficient test, determinant coefficient test, heteroscedasticity test, multiple linear regression test, T test and F test. The results of this study indicate that financial literacy factors, income levels and financial experience have a significant effect on financial behavior partially. Simultaneously, financial literacy factors, income levels and financial experience have a 57.8% influence on financial behavior with 42.2% influenced by other factors not discussed in this study.